2013
DOI: 10.1099/jmm.0.055566-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Candida species resistant to azoles in the microbiota of rheas (Rhea americana): possible implications for human and animal health

Abstract: There is growing interest in breeding rheas (Rhea americana) in Brazil. However, there are no data on the yeast microbiota of the gastrointestinal tract of this avian species, and the phenotypic characteristics of these yeasts are not known. Therefore, the aim of this work was to isolate Candida species from the digestive tract of rheas and to evaluate the in vitro antifungal susceptibility and secretion of phospholipases of the recovered isolates. For this purpose, 58 rheas from breeding operations in the cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
34
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 37 publications
5
34
3
1
Order By: Relevance
“…The results found in this study are in clear contrast with those of previous reports that reveal alarmingly high rates of azole resistance among Candida strains of veterinary origin (6)(7)(8)(9)(10)(11)(12)(13). Notably, 47.8% of our isolates were collected between 2008 and 2014, when the first reports of substantial prevalence of azole resistance among yeast isolates obtained from animals were being published.…”
contrasting
confidence: 56%
See 2 more Smart Citations
“…The results found in this study are in clear contrast with those of previous reports that reveal alarmingly high rates of azole resistance among Candida strains of veterinary origin (6)(7)(8)(9)(10)(11)(12)(13). Notably, 47.8% of our isolates were collected between 2008 and 2014, when the first reports of substantial prevalence of azole resistance among yeast isolates obtained from animals were being published.…”
contrasting
confidence: 56%
“…The results of some recent studies of yeast collections of animal origin suggest that azole resistance is also relatively common among isolates from diverse host species and that even healthy individuals can serve as a reservoir of resistant strains (6)(7)(8)(9)(10)(11)(12)(13). For example, Cordeiro et al (10) found resistance rates of Ͼ45% for fluconazole and itraconazole, and a 37.5% rate of cross-resistance to both compounds, in a Brazilian collection of 64 Candida tropicalis isolates obtained from several animal species.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with strains from animals, developed by our group, have detected the emergence of azole resistance in Candida spp. recovered from several animal species, especially C. albicans, demonstrating the importance of researches assessing this subject [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…However, our group has recovered azole-resistant C. albicans from several animal species [12][13][14][15]. Therefore, this study aimed to reidentify these isolates, focusing on evaluating the accuracy of combined phenotypic tests for the differentiation of C. albicans and C. dubliniensis, using the polymerase chain reaction (PCR)-based identification as gold standard.…”
Section: Introductionmentioning
confidence: 99%